Smallholder dairying under transactions costs in East Africa - Staal, Steven; Delgado, Christopher L.; Nicholson, Charles F. (International Food Policy Research Institute, 1996)
It is argued that dairying is vital to future viability of many small farms in East Africa and that high transactions costs for dairy production and marketing limit participation by asset- and information-poor smallholders. Case studies from Kenya and Ethiopia illustrate the role of dairy cooperatives in reducing transactions costs. Analysis of the determinants of producer prices received by a sample of dairy producers near Addis Ababa suggests that different levels of access to infrastructure, assets, and information explain why different households contemporaneously accept widely different producer prices for fluid milk.